2016
DOI: 10.2217/pmt-2016-0038
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Sulfate on Morphine Activity Retention to Control Pain After Herniorrhaphy

Abstract: MgSO increased the potency of morphine thereby reducing the amount of postoperative pain killer needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, PCL was used as a good polymer to fabricate the shell structure of the nanofibrous scaffold due to its history of being successfully electrospun into porous structure and able to provide stem cell proliferation and differentiation. 23,24 These results suggest that the core-shell structure of PEG/PCL had effects on the release profile of PEDF factor. 10,25 This could support the hypothesis that coaxially spun fibers are more suitable for sustained release of growth factor over time.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, PCL was used as a good polymer to fabricate the shell structure of the nanofibrous scaffold due to its history of being successfully electrospun into porous structure and able to provide stem cell proliferation and differentiation. 23,24 These results suggest that the core-shell structure of PEG/PCL had effects on the release profile of PEDF factor. 10,25 This could support the hypothesis that coaxially spun fibers are more suitable for sustained release of growth factor over time.…”
Section: Discussionmentioning
confidence: 81%
“…We developed biocompatible and biodegradable poly ( ɛ ‐caprolactone) (PCL) as sell structure of coaxial fibrous scaffold. However, PCL was used as a good polymer to fabricate the shell structure of the nanofibrous scaffold due to its history of being successfully electrospun into porous structure and able to provide stem cell proliferation and differentiation . These results suggest that the core‐shell structure of PEG/PCL had effects on the release profile of PEDF factor .…”
Section: Discussionmentioning
confidence: 99%
“…However, they stated that auxiliary care and treatment for chronic pain relief is required for the patients [44]. In another clinical study carried out by Manvelian and co-worker, phase 1, single-center, single-dose, randomized, study to investigate the pharmacokinetics parameters of a nano-formulated, lower-dose diclofenac compared to a standard diclofenac dose in healthy patients [45]. They reported that the nano-fabricated diclofenac increased absorption rate compared to standard diclofenac.…”
Section: Nano-diclofenac and Chronic Painmentioning
confidence: 99%
“…Electrolytes are charged elements in the body that are crucial for proper functioning of body tissues and organs. Dysfunction in the levels of electrolytes is associated with several morbidities and present life-threatening risk [ [1] , [2] , [3] ]. In these cases, rapid measurement of electrolytes is required to provide immediate treatment.…”
Section: Introductionmentioning
confidence: 99%